Antiretroviral Therapy With Efavirenz Accentuates Pregnancy‐Associated Reduction of Dihydroartemisinin‐Piperaquine Exposure During Malaria Chemoprevention. Issue 3 (30th May 2017) - Kajubi, R; Huang, L; Jagannathan, P; Chamankhah, N; Were, M; Ruel, T; Koss, CA; Kakuru, A; Mwebaza, N; Kamya, M; Havlir, D; Dorsey, G; et al.
Abstract : Dihydroartemisinin (DHA)‐piperaquine is promising for malaria chemoprevention in pregnancy. We assessed the impacts of pregnancy and efavirenz‐based antiretroviral therapy on exposure to DHA and piperaquine in pregnant Ugandan women. Intensive sampling was performed at 28 weeks gestation in 31 HIV‐uninfected pregnant women, in 27 HIV‐infected pregnant women receiving efavirenz, and in 30 HIV‐uninfected nonpregnant women. DHA peak concentration and area under the concentration time curve (AUC0‐8hr ) were 50% and 47% lower, respectively, and piperaquine AUC0‐21d was 40% lower in pregnant women compared to nonpregnant women. DHA AUC0‐8hr and piperaquine AUC0‐21d were 27% and 38% lower, respectively, in pregnant women receiving efavirenz compared to HIV‐uninfected pregnant women. Exposure to DHA and piperaquine were lower among pregnant women and particularly in women on efavirenz, suggesting a need for dose modifications. The study of modified dosing strategies for these populations is urgently needed.